1982
DOI: 10.1056/nejm198206243062502
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Indium-111 Platelet Scintigraphy and Two-Dimensional Echocardiography in the Diagnosis of Left Ventricular Thrombi

Abstract: In a study comparing indium-111 platelet scintigraphy and two-dimensional echocardiography as methods of identifying left ventricular thrombi, the results obtained with both techniques were verified at surgery or autopsy in 53 patients--34 with left ventricular aneurysms, and 19 with mitral-valve disease. Left ventricular thrombi were found at surgery or autopsy in 14 of the patients with aneurysms and in none of those with mitral-valve disease. Thirteen of 53 echocardiograms (25 per cent) were technically ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

1983
1983
1996
1996

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(19 citation statements)
references
References 15 publications
0
18
1
Order By: Relevance
“…The sensitivity of 2-DE for diagnosis of thrombus appears to be between 77% 28 and 92% 29 in patients with ventricular lesions and may be even lower for atrial disease. 29 - 30 In addition, 2-DE may be of limited value secondary to technical difficulties in 10-20% of investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of 2-DE for diagnosis of thrombus appears to be between 77% 28 and 92% 29 in patients with ventricular lesions and may be even lower for atrial disease. 29 - 30 In addition, 2-DE may be of limited value secondary to technical difficulties in 10-20% of investigations.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Several retrospective reports have suggested a high incidence of left ventricular thrombosis in patients who have had peripheral emboli after a myocardial infarction. ' 4 5 In one prospective study,6 a high incidence of left ventricular thrombosis in acute anterior wall infarctions was found, but peripheral emboli were not diagnosed.…”
mentioning
confidence: 99%
“…A study by Stratton and colleagues that included 78 patients with independent documentation of either the presence or absence of thrombus (surgery/autopsy) identified a diagnostic sensitivity of 95% and a specificity of 86% [11]. An overview of five studies performed between 1981 and 1982 utilized postmortem or surgical findings for comparison and found that echocardiography had an overall sensitivity of 87% and a specificity of 75% ( [1,[11][12][13][14][15].…”
Section: Detection and Diagnostic Evaluation Of Cardiac Thrombusmentioning
confidence: 99%